Review on dislodgement & securement risk of peripheral intravenous Catheter/Cannula and the needs of PIVC securement device - Zainul Fadziruddin, Zubair Faramir; Basr, Adi Azriff; Basri, Ernnie Illyani (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Intravenous (IV) infusion of medical fluid is a very common procedure used as part of medical procedure treatment. It is also the best alternative medical administration route when medical administration through orally is impossible. The most common use of VAD is the short Peripheral IV Catheter (PIVC) or recognized as IV Cannula. In spite of that, even with experience used of PIVC in medical practice nowadays the rate of IV access failure is very high which is up to 69%. Intensive research studies shows the dislodgement case is one of the major contributions of PIVC failure. For some reason only a fewer cases are reported to the administration. This article seeks the awareness and risk factor regarding to the prevailing IV access failure using the PIVC. This manuscript reviewed the statistical data of PIVC dislodgement, significant of dislodgement, dislodgment cases among pediatric, medical staff factor related to PIVC dislodgement and alternative of securement device. This manuscript also discussed the needs of new securement device in order to reduce the percentage of PIVC dislodgement from occurs.